Coupled Short- and Medium-Term Geophysical Signals at Etna Volcano: Using Deformation and Strain to Infer Magmatic Processes From 2009 to 2017 - Aloisi, Marco; Bonaccorso, Alessandro; Cannavò, Flavio; Currenti, Gilda M. (Frontiers in Earth Science, 2018)
In active volcanoes a main challenge is to identify and characterize the dynamics of magmatic sources from deformation and strain data. This task is of primary importance in frequently eruptive volcanoes, such as Etna. After the main flank eruption of 2008–2009 and until 2017, Etna volcano was characterized by a lively eruptive activity of different phases. These comprised 44 lava fountain episodes from the New South East Crater (NSEC), two sequences of close episodes of lava fountains from the Voragine crater (VOR), as well as some periods of summit effusive activity with a more prolonged supply of lava flows. Several studies have described and modeled single lava fountains episodes of the NSEC and VOR, in particular through high precision data from borehole strain-meters. In this study, we broaden the analysis also considering the medium-term volcano recharging/discharging periods preceding/accompanying the different eruptive phases during 2009–2017 by constraining the source positions through deformation recorded by the permanent GPS network. Together with the modeling deduced from the strain-meter data we produce a more complete representation of the different sources that characterized the different periods both in the medium-term (i.e., the preparatory phases showing inflation and the eruptive phases showing deflation) and in the short-term (i.e., the fast discharge associated with eruptive events). Our modeling explains the pathway of magma from the intermediate-shallow plumbing system to the surface and highlights a clear separation between the inflation and the deflation source depths, coherently with petrological constraints on the spatio-temporal evolution of magma transfer and storage.